2018
DOI: 10.1111/gcb.14016
|View full text |Cite
|
Sign up to set email alerts
|

‘Stick with your own kind, or hang with the locals?’ Implications of shoaling strategy for tropical reef fish on a range‐expansion frontline

Abstract: Range shifts of tropical marine species to temperate latitudes are predicted to increase as a consequence of climate change. To date, the research focus on climate-mediated range shifts has been predominately dealt with the physiological capacity of tropical species to cope with the thermal challenges imposed by temperate latitudes. Behavioural traits of individuals in the novel temperate environment have not previously been investigated, however, they are also likely to play a key role in determining the esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 88 publications
0
57
0
Order By: Relevance
“…In addition to our findings, support for fitness benefits associated with mixed‐species shoaling is provided by Smith et al . (), who found that vagrant A. vaigiensis within mixed‐species shoals displayed increased growth rates relative to those within single‐species shoals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to our findings, support for fitness benefits associated with mixed‐species shoaling is provided by Smith et al . (), who found that vagrant A. vaigiensis within mixed‐species shoals displayed increased growth rates relative to those within single‐species shoals.…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al . () found that A. vaigiensis within mixed‐species shoals had a higher growth rate than those in single‐species shoals. However, they found no differences between the size of mixed‐ and single‐species shoals or between the distance from shelter for A. vaigiensis within each shoal type.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations